Phytochemical screening and antioxidant activity of Gyrinops tea from agarwood plantation on Lombok island, Indonesia. Issue 1 (March 2021) - Wangiyana, I G A S; Supriadi,; Nikmatullah, A; Sunarpi,; Putri, D S; Rosidah, and S
Abstract: Phytochemical screening and antioxidant analysis are essential standardization procedure for the agarwood tea product. Gyrinops tea is an agarwood tea that has been emerged on Lombok Island recently. This research aims to carry qualitative phytochemical analysis and antioxidant activity assay of Gyrinops tea from several agarwood plantations on Lombok Island. Gyrinops versteegii leaves as the raw material of Gyrinops tea were taken from several agarwood plantations on Lombok Island, including Lingsar, Rarung, Kekait, Pejaring, and Mataram. There are three steps on G. versteegii leaves processing method into Gyrinops tea, including sterilization, drying, and chopping. G. versteegii leaves were brewed in distilled water at 70°C for 5 minutes to make Gyrinops tea. Phytochemical screening of Gyrinops tea was conducted with a qualitative assay identification of Flavonoid, Alkaloid, Saponin, and Tannin. The antioxidant assay of Gyrinops tea was investigated based on DPPH radicals scavenging activity. The result shows that Gyrinops tea positively contains tannin in high dosage and Flavonoid in a moderate dose with no alkaloid and saponin. Gyrinops tea samples have various antioxidant activity from moderate to strong based on IC50 measurement. It could be concluded that different sampling location has affected antioxidant activity of Gyrinops tea.